Chinese Residents' Subjective Class Identity and Physical Activity Participation Mechanism - Yang, Chuangjian; Li, Zhifu; Liu, Wei (Frontiers in Public Health, 2022)
The aim of the present study was to evaluate the association between participation in physical activity and subjective class identity of people in urban and rural areas of China. The effect of social class identity on residents' physical activity was tested using the Monte Carlo method. There is a positive correlation between physical activity and the subjective class identity of urban and rural residents (r = 0.351, p < 0.01). It has been also seen that subjective class identity can significantly improve residents' physical activity. The path coefficient of subjective class identity to residents' physical activity was 0.12 (p < 0.003). Therefore, national and local governments should promote the equalization of physical activities by providing public services and government transfer payments in urban and rural areas, improve the physical activity by improving subjective class identity and promote social progress.